Citizen Participation in Realizing Gender Equality in Education And Development - Alif Aditya Candra; Aulia Sholichah Iman Nurchotimah; Mochammad Tholluth Syaifulloh (CV. Rayyan Dwi Bharata, 2022)
This study aims to examine how the concept of citizen participation in realizing gender equality. The method used in this research was a literature study. The results of the study show that citizen participation in realizing gender equality is very important, participating in the education sector by seeking to create educational institutions that produce future leaders who do not discriminate against gender nor have a gender justice perspective. Citizens can participate in encouraging social inclusion in the classroom when learning process takes place, designing inclusive and gender sensitive-curricula as well as providing equal opportunities for men and women. Citizen participation in the field of development to realize gender equality can be carried out by planning and making development policies and implementing policies that provide equal opportunities without any gender discrimination. This research concludes that realizing the gender equality as a form of citizen rights requires participation of all citizens in various forms both in the fields of education and development.